Metaphor as a Means of Representation and Modeling of Concept “Failure” Verbalized By English Idioms - Vinogradova, Ekaterina A.; Shevchenko, Elena M.; Mashkova, Elena V.; Kislitsyna, Elena V.; Kuptsova, Yulia A. (Journal of History Culture and Art Research, 2018)
The article deals with the peculiarities of phraseological representation of the concept “failure” in the English language. Special emphasis is placed on the semantic features of the idioms and the image basis in their semantic structure. Special attention is given to a prototype and metaphor, representing different spheres of human life. In this paper, the functioning of idioms in discourse is also under study. In the course of study we found out that the basis of the images of numerous idioms representing concept “failure” is formed by such metaphors as animalistic, ornithological, spatial, color, gastronomic, temperature, numerical, machine, and military.